Dissipation of fenitrothion and esfenvalerate in wheat grains, bran and flour - Vásquez-Castro, J. (2020)
Chemical insecticides are commonly used to control insect pests in stored wheat. However, the presence of insecticide residues in food may endanger consumers. We studied the degradation and persistence of two insecticides, fenitrothion and esfenvalerate, in wheat grain, bran, and flour. The application system was calibrated to treat grain at theoretical concentrations of 10 and 0.5 mg kg−1 of fenitrothion and esfenvalerate, respectively. Samples treated with the insecticide mixture were collected at 0, 15, 30, 60, 90, 120, 180, 240, and 360 days after treatment. Samples were analyzed quantitatively by gas chromatography with an electron capture detector (ECD, Ni63). The experimental design was completely randomized with three replicates. Esfenvalerate was more persistent than fenitrothion, with the residues of both insecticides concentrated mainly in the bran, and with least amounts in the flour. The concentrations of fenitrothion residues during the 120-day preharvest interval exceeded the maximum residue limit (MRL) of 1 mg kg−1 set by Brazilian legislation. We discuss the factors that influence the degradation/persistence of fenitrothion and esfenvalerate.